2019
DOI: 10.1590/1678-5150-pvb-5814
|View full text |Cite
|
Sign up to set email alerts
|

Causes of death and euthanasia in domestic cats in the Santa Catarina plateau (1995-2015)

Abstract: Knowledge about the causes of death in felines constitutes important information to owners, veterinarians, and researchers, aiming at reducing the number of deaths in this species. In order to determine the main causes of death or euthanasia in cats in the Santa Catarina plateau, data from 1995 to 2015 available in necropsy files of the Laboratory of Animal Pathology (LAPA) of the State University of Santa Catarina (UDESC) were collected and evaluated. In that period, 1,728 cats were necropsied, mainly males (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 20 publications
3
6
1
Order By: Relevance
“…Neoplasms were the third most relevant cause of death, consistent with other studies where neoplasms had similar frequencies and were consistently among the top four causes of death (BENTUBO et al, 2007;FIGHERA et al, 2008;TRAPP et al, 2010;BATISTA et al, 2016;ROLIM, 2017;TOGNI et al, 2018;WITHOEFT et al, 2019;DE FREITAS et al, 2021). There was no significant association between neoplasms and the animal's sex, age group, or breed.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…Neoplasms were the third most relevant cause of death, consistent with other studies where neoplasms had similar frequencies and were consistently among the top four causes of death (BENTUBO et al, 2007;FIGHERA et al, 2008;TRAPP et al, 2010;BATISTA et al, 2016;ROLIM, 2017;TOGNI et al, 2018;WITHOEFT et al, 2019;DE FREITAS et al, 2021). There was no significant association between neoplasms and the animal's sex, age group, or breed.…”
Section: Resultssupporting
confidence: 86%
“…The latest National Health Survey in Brazil, conducted in 2013, found that the population of dogs and cats in the country was approximately 52 million and 22 million, respectively, with a tendency for population growth (INSTITUTO BRASILEIRO DE GEOGRAFIA E ESTATÍSTICA, 2015). However, there are few reports of studies focused on the causes of death in dogs and cats in Brazil and worldwide (BENTUBO et al, 2007;FIGHERA et al, 2008;TRAPP et al, 2010;BATISTA et al, 2016;ROLIM, 2017;TOGNI et al, 2018;WITHOEFT et al, 2019;DE FREITAS et al, 2021). In fact, among the extensive literature consulted, no studies were found in the state of Espírito Santo, where the present research was conducted.…”
Section: Introductionmentioning
confidence: 90%
“…The present study also demonstrated the absence of a breed predisposition; however, most cats were of no defined breed, which is consistent with the population of domestic cats in this geographic area. 11 The most common locations described in the literature are the interscapular region, flank and lateral thorax, consistent with sites of vaccination and drug application, which leads to the assumption that most diagnosed PSs are histologic variants of FISS. 2,7 Similar findings were reported in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…The present study also demonstrated the absence of a breed predisposition; however, most cats were of no defined breed, which is consistent with the population of domestic cats in this geographic area. 11…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, heart disease in cats was found to have a frequency of 4.2 to 5.7% (O'neill et al 2014(O'neill et al , Rodrigues et al 2017. In studies of the causes of death and reasons for euthanasia, cardiomyopathies accounted for approximately 1% of total feline necropsies (Togni et al 2018, Withoeft et al 2019. In cats, cardiomyopathies are the most frequent cardiovascular diseases and are important causes of death in the species (Ferasin 2009a).…”
Section: Discussionmentioning
confidence: 99%